Generation and dissociation pathways of singly and doubly protonated bisguanidines in the gas phase - Tintaru, Aura; Roithová, Jana; Schröder, Detlef; Charles, Laurence; Jusinski, Iva; Glasovac, Zoran; Eckert-Maksić, Mirjana (The journal of physical chemistry. A, 2008)
Para-bisguanidinyl benzene 1 and its N-permethylated derivative 2 are both sufficiently strong bases to afford not only the monocations [1+H]+ and [2+H]+, but also the doubly protonated ions, [1+2H]2+ and [2+2H]2+, in the gas phase. The title ions generated via electrospray ionization are probed by collision-induced dissociation experiments which inter alia reveal that the dicationic species [1+2H]2+ and [2+2H]2+ can even undergo fragmentation reactions with maintenance of the 2-fold charge. Complementary results from density functional theory predict PAs above 1000 kJ mol(-1) for the neutral compounds, i.e., PA(1) = 1025 kJ mol(-1) and PA(2) = 1067 kJ mol(-1). Due to the stabilization of the positive charge in the guanidinium ions and the para-phenylene spacer separating the basic sites, even the monocations bear sizable proton affinities, i.e., PA([1+H]+) = 740 kJ mol(-1) and PA([2+H]+) = 816 kJ mol(-1).
Keywords: chemické modely; Guanidines; hmotnostní spektrometrie s elektrosprejovou ionizací; plyny; Spectrometry, Mass, Electrospray Ionization; protony; Gases; guanidiny; Models, Chemical; Protons